2020
DOI: 10.1108/ijbm-04-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

A citizen-centred approach to CSR in banking

Abstract: PurposeThis study aims to demonstrate how banks can align their CSR investment to community needs and citizen preferences. A grounded theory inductive approach is applied to deliver a community-centred process that banks can apply to inform CSR investment decisions.Design/methodology/approachThis study employed a sequential mixed-method research design to identify areas of need from the perspective of community leaders and members through depth interviews. Following thematic analysis, citizen preferences for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
7
1
Order By: Relevance
“…Our findings differed from van Hierden et al [48] who noted that communities in Australia preferred infrastructure, crisis, and prevention support, while this research found that the local community preferred CSR activities that improved the economy and the environment. One probable explanation for this disparity is the context of this study, which was located in a developing nation, i.e., Thailand.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings differed from van Hierden et al [48] who noted that communities in Australia preferred infrastructure, crisis, and prevention support, while this research found that the local community preferred CSR activities that improved the economy and the environment. One probable explanation for this disparity is the context of this study, which was located in a developing nation, i.e., Thailand.…”
Section: Discussioncontrasting
confidence: 99%
“…CSR can be viewed as a mediating role for companies [36] to manifest societal values and accountabilities, balance stakeholder interests, and regain trust from the community [34]. Many studies have emphasized the importance of local communities (e.g., Chapple and Moon [45] and Srisuphaolarn [7]) but very few studies have investigated the preferred CSR activities of local residents (e.g., van Hierden [48]). This limited understanding of CSR preferences presents the research gap that this study fills by answering the research question "What are the preferred CSR dimensions of residents living in the vicinity of IEs?…”
Section: Dimensions Of Corporate Social Responsibility (Csr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable attention has been paid to CSR activities in the banking sector (Fatma and Rahman, 2016). Nowadays, Indian banks are also investing their money into community welfare programmes and solving social and environmental problems (Rugimbana et al , 2008; van Hierden et al , 2020). Banks have started to increase their spending on CSR activities (Marin et al , 2009) and become proactive investors in socially responsible activities (He and Li, 2011).…”
Section: Methodsmentioning
confidence: 99%